Beyond the hindrances: experiences of public consultations and the possibility of ethics and relevance in participation - Fernandes-Jesus, M.; Seixas, E. C.; Carvalho, A. (Comunicação e Sociedade, 2019)
Public consultations are increasingly used in projects with environmental impact, allegedly as a way to ensure that affected people and communities have their concerns recognised and addressed. There have been multiple criticisms of this form of public participation, with consultations frequently viewed as a tokenistic practice. In this study, we focus on a public consultation on extra-high voltage power lines projected to go from northern Portugal to northwestern Spain. We analyse citizens’ discourses regarding hindrances to participation as well as envisaged possibilities to improve it. The study draws on semi-structured interviews with 26 people and five focus groups discussions (N=37) carried out in localities in the north of Portugal that would be affected by the project. Based on citizens’ narrated experiences of participation we discuss the relevance and the ethics of participation in access, standing and influence in public consultations processes.